AB0461 Efficacy of Abatacept Intravenous. Study of 45 Patients. (9th June 2015) - Bejerano, C.; Pertega, S.; Pinto-Tasende, J.A.; Oreiro, N.; Alonso, E.; Silva-Diaz, M.T.; Gromaz, J.; Soilán, A.; Rey, R.; Gismero, E.; De Toro, F.J.; Blanco, F.J.; et al.
Abstract : Objectives: To assess the probability of withdrawal Abatacept intravenous (i.v) due to lack of efficacy and identify variables related to the survival to treatment. Methods: A Retrospective, observational, open and non controlated study of clinical records of 45 patients in a third level Hospital in Northwest Spain who have been treated with Abatacept i.v in the last ten years. Statistical analysis: A descriptive analysis was performed. Compliance probability was estimated by means of Kaplan-Meier survival curves, and compared with the log-rank test. Results: We studied 45 patients with a mean age at the beginning of 48, 8±16, 7 years and time of evolution of the disease 12.0±7, 9 years. 80% were women (36 patients). 75, 6% (34 patients) were Rheumatoid Arthritis, 13, 3% (6) Juvenile Idiopathic Arthritis and 11.1% (5) Psoriatic Arthritis. Rheumatoid Factor (RF) was positive in 52% (28) and in 62.2% (28) the disease was erosive. Thirty five patients had combination therapy with conventional DMARDs: Azathioprine in 2 cases, 8 patients with Leflunomide and Methotrexate in 25 cases. 21 patients (46, 7%) had glucocorticoids. Initially, 20, 0% of cases were biologic naive, 37, 8% were failure of one biologic DMARD and failure of two or more in 41, 2%. Eighteen patients (40%) withdrawal Abatacept because lack of efficacy in nine patients and nine had an adverse event. Probability to continue the treatment without lack of efficacy at two years was 84, 0%, at 5 years 70, 9% and it is kept ten years after treatment. Probability of withdrawal Abatacept was minor in patients with positive RF (p=0, 042), erosive disease (p=0, 068), biologic naive (p=0, 052) or patients who have received less than two biologic DMARDs (p=0, 007). Conclusions: The most of patients who had initiated Abatacept intravenous have continued the treatment ten years after. Probability of withdrawal due to lack of efficacy was minor in patients with positive RF, erosive disease or patients who have received less than two biologic DMARDs. Disclosure of Interest: None declared